Education marketing mix for private vocational high schools in Indonesia - Panditatwa, Panduaji; Hidayat, Anas (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
Private vocational high schools (VHS) in Indonesia are crucial to the education system yet facing unique marketing challenges that have not been adequately studied. This study aims to develop tailored marketing mix elements for private VHS institutions in Indonesia, providing valuable insight for education marketing studies and enhancing the competitiveness of these institutions in the education service landscape. This study utilises an inductive approach with an exploratory design. It leverages existing data to address marketing mix issues specific to private VHS institutions. Key stakeholders in the private VHS sector were engaged for insights and expert judgement was employed for validation. Pilot testing involving 37 students assessed the instrument's validity and reliability. The study retains a total of 60 components from the seven marketing mix elements. Further validation through robust tools like confirmatory factor analysis (CFA) is necessary to ensure the accuracy and applicability of these elements. This study introduces novel marketing mix elements tailored to private VHS institutions in Indonesia, filling a significant gap in education marketing studies by offering a customised approach that can potentially transform strategies, enhance market impact, and provide substantial substance for analytical tools. The proposed elements can reshape marketing for private VHS institutions, boosting competitiveness and market presence, providing valuable insights for informed decisions and fostering sustainable growth in the dynamic education landscape. Limitations of this study lies in its focus on private VHS institutions implementing the Ministry of Education's centre of excellence program, potentially generalising the formulated elements, requiring further inquiry for adaptation to diverse private VHS contexts.